Stability and Electronic Characteristics of Epitaxial Silicene Multilayers on Ag(111). (22nd May 2015) - Johnson, Neil W.; Muir, David; Kurmaev, Ernst Z.; Moewes, Alexander
<x xml:space="preserve">Abstract</x> In this study, the stability and electronic characteristics of epitaxial silicene bilayers and multilayers on the Ag(111) surface are investigated through synchrotron‐based soft X‐ray emission and absorption spectroscopy and first‐principles, full‐potential density functional theory simulations. The calculations predict a novel tristable AA‐stacked bilayer structure that can explain the (√3 × √3)R30° honeycomb topography commonly observed through scanning tunneling microscopy and noncontact atomic force microscopy. It is reported that the electronic structure of this epitaxial bilayer is similar to those of epitaxial monolayers on Ag(111), namely, metallic and showing significant interaction with the underlying substrate. However, the soft X‐ray spectroscopy experiments suggest that during multilayer growth a majority of the epitaxial silicon reverts to a bulk‐like state, a result that has significant implications toward the existence of large‐area epitaxial silicene multilayers.